2012
DOI: 10.1016/j.bbadis.2012.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic cleavage of the disease-related lysosomal membrane glycoprotein CLN7

Abstract: CLN7 is a polytopic lysosomal membrane glycoprotein of unknown function and is deficient in variant late infantile neuronal ceroid lipofuscinosis. Here we show that full-length CLN7 is proteolytically cleaved twice, once proximal to the used N-glycosylation sites in lumenal loop L9 and once distal to these sites. Cleavage occurs by cysteine proteases in acidic compartments and disruption of lysosomal targeting of CLN7 results in inhibition of proteolytic cleavage. The apparent molecular masses of the CLN7 frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 59 publications
2
35
1
Order By: Relevance
“…39,46,47 Studies in gene-targeted mouse embryonic fibroblasts show that MFSD8 is asymmetrically double cleaved for proper function. 48 Analysis of 2 missense mutations demonstrates that the cleavage occurs in the luminal L9 loop, and the proteolytic cleavage is altered by these mutations. 48 The c.1102G>C mutation induces a splice defect and skipping of exon 11, resulting in a truncated protein (p.Lys333Lysfs*3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39,46,47 Studies in gene-targeted mouse embryonic fibroblasts show that MFSD8 is asymmetrically double cleaved for proper function. 48 Analysis of 2 missense mutations demonstrates that the cleavage occurs in the luminal L9 loop, and the proteolytic cleavage is altered by these mutations. 48 The c.1102G>C mutation induces a splice defect and skipping of exon 11, resulting in a truncated protein (p.Lys333Lysfs*3).…”
Section: Discussionmentioning
confidence: 99%
“…48 Analysis of 2 missense mutations demonstrates that the cleavage occurs in the luminal L9 loop, and the proteolytic cleavage is altered by these mutations. 48 The c.1102G>C mutation induces a splice defect and skipping of exon 11, resulting in a truncated protein (p.Lys333Lysfs*3). Nevertheless, a wild-type transcript lacking exon 11 was seen in a control sample, suggesting that this event also occurs naturally, although more normal transcript (containing exon 11) was observed in the control sample compared with affected individual B:II-1.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this idea, many soluble lysosomal enzymes including TPP1 (CLN2), CTSD (CLN10), CTSF (CLN13), and acid alpha-glucosidase undergo proteolytic cleavage and maturation in the lysosomes [32–36]. Another NCL polytopic membrane protein, CLN7, has also been observed to undergo cysteine pro-tease-dependent proteolytic cleavage in the lysosome [37]. Further investigation will be needed to understand the importance of CLN5 proteolytic processing and to reveal the function of CLN5.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that some of the missense alleles may represent functional null mutations. 36 Based on the pathogenicity prediction scores of the missense mutations (Supplementary Table S2) and the topology prediction diagram that maps the mutations on the protein sequence (Fig. 5) there appears to be no obvious correlation between the mutations and whether the patient develops vLINCL or nonsyndromic eye disease.…”
Section: Figurementioning
confidence: 99%